FILSAFAT KETUHANAN DALAM YOGA DARSANA - Luh Kartika Dewi; Ni Putu Sinta Oktaviani; Putu Eka Arsadi (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
The journal is titled Divine Philosophy in Darsana Yoga compiled with various understandings. This title was chosen based on the author's idea, this journal focuses on what Drarsana Yoga is. The author takes this title aiming that those who read this journal can understand what the essence of the journal he made is the Divine Philosophy in Yoga Darsana. Here we review about God, what is a true God in the Darsana Yoga Divinity of Yoga. God philosophy is thinking about God with the mind approach, for people who adhere to a particular religion will add to the revelation approach in the business of thinking. The Philosophy of God is the thinking of human beings with an approach to reason about God that humans do is not to find an absolute God or absolute, but to seek consideration for humans to arrive at the truth about God.